Cellular prion protein in blood platelets associates with both lipid rafts and the cytoskeleton - Brouckova, Adela; Holada, Karel (Thrombosis and haemostasis, 2009)
The recently shown transmissibility of variant Creutzfeldt-Jakob disease (vCJD) by blood transfusion emphasises the need for better understanding of the cellular prion protein (PrPc) in blood. A substantial amount of cell-associated PrPc in blood resides in platelets. Platelet activation leads to up-regulation of PrPc on the platelet surface and its release on exosomes and microparticles. The sub-cellular localisation and function of platelet PrPc, however, is poorly understood. In the present study, we investigated the association of PrPc with platelet lipid rafts and the platelet cytoskeleton. Immuno-fluorescence microscopy showed that the signals of PrPc and P-selectin, both of which occupy intracellular alpha granules, were separated on the membrane, suggesting organisation in different membrane domains. A flotation assay of platelet lysates demonstrated that a relatively small portion of platelet PrPc floats with lipid rafts, regardless of platelet activation status. This was reversed by depolymerisation of the platelet cytoskeleton, which led to flotation of most platelet PrPc, suggesting that interactions with the cytoskeleton prevent flotation of PrPc rafts. This association of PrPc with the platelet cytoskeleton was confirmed by its presence in both the isolated membrane skeleton and actin cytoskeleton. Platelet activation significantly increased the amount of PrPc associated with the cytoskeleton. Our results indicate that the localisation of PrPc in platelets is complex, with the majority of PrPc present within platelet lipid rafts linked to the platelet cytoskeleton. This localisation places PrPc in a position where it can interact with proteins involved in platelet signalling and eventually with vCJD prions.
Keywords: membránové mikrodomény; buněčná membrána; Microscopy, Fluorescence; cytoskelet; Humans; Biopolymers; Platelet Activation; biopolymery; fluorescenční mikroskopie; trombocyty; P-selektin; lidé; Cytoplasmic Granules; P-Selectin; PrPC proteiny; Blood Platelets; aktivace trombocytů; Cell Membrane; Membrane Microdomains; cytoplazmatická granula; Cytoskeleton; PrPC Proteins